LEADERSHIP STRATEGIES OF MADRASAH HEADS IN TEAMWORK MANAGEMENT AT MIN 20 ACEH BESAR - Mardin Mardin; Hikmah Mardyanto (STAI Nusantara Kota Banda Aceh, 2026)
This study aims to examine the strategies and challenges of the principal’s leadership in managing teamwork at MIN 20 Aceh Besar, while comparing its practices with previous findings by Dewi (2021) and Munandar (2022). Employing a qualitative approach, data were collected through observation, interviews, documentation, and triangulation involving various school stakeholders. The findings reveal that the principal's leadership strategies are implemented in a collaborative, participatory, and contextual manner rooted in the school's work culture. These strategies include joint planning, team involvement in task distribution, competency-based delegation, and clearly defined authority. Regular monitoring and evaluation are conducted, along with capacity building through structured training programmes. The main challenges identified are inconsistent commitment levels among team members and limited technical skills. Nonetheless, mutual trust among members has been well-established. Communication obstacles have been addressed through regular coordination and deliberation forums. The headteacher continues to enhance team performance through structured training and development efforts aimed at overcoming limitations and strengthening collaborative commitment.